Cardiopulmonary Function, Exercise Capacity, and Echocardiography Finding of Pediatric Patients With Kawasaki Disease: An Observational Study. Issue 2 (January 2016) - Tuan, Sheng-Hui; Li, Min-Hui; Hsu, Miao-Ju; Tsai, Yun-Jeng; Chen, Yin-Han; Liao, Tin-Yun; Lin, Ko-Long
Abstract : Abstract: Coronary artery (CA) abnormalities influence exercise capacity (EC) of patients with Kawasaki disease (KD), and Z-score of CA is a well established method for detecting CA aneurysm. We studied the influence of KD on cardiopulmonary function and EC; meanwhile we analyzed echocardiographic findings of KD patients. We also assessed the correlation between CA Z-score and EC of KD patients to see if CA Z-score of KD patients could reflect EC during exercise. Sixty-three KD patients were recruited as KD group 1 from children (aged 5–18 y) who received transthoracic echocardiographic examinations and symptom-limited treadmill exercise test for regular follow-up of KD from January 2010 to October 2014 in 1 medical center. We then divided KD group 1 into KD group 2 (<5 y, n = 12) and KD group 3 (≥5 y, n = 51) according to time interval between KD onset to when patients received test. Control groups were matched by age, sex, and body mass index. Max-Z of CA was defined as the maximal Z-score of the proximal LCA or RCA by Dalliarre equation or Fuse calculator. All routine parameters measured during standard exercise test were similar between KD and control groups, except that peak rate pressure products (PRPPs) in KD group 1 to 3 were all lower than corresponding control groups significantly ( P = 0.010, 0.020, and 0.049, respectively). PRPPs correlated with Max-Z of CA by both equations modest inversely (by Dallaire, P = 0.017, Spearman rho = −0.301; by Fuse, P = 0.014, Spearman rho = −0.309). Our study recruited larger number of KD patients and provided a newer data of EC of KD patients. Our finding suggests that after acute stage of KD, patients could maintain normal cardiorespiratory fitness. Therefore, we believe that it is important to promote cardiovascular health to KD patients and KD patients should exercise as normal peers. However, since KD patients might still have compromised coronary perfusion during exercise, it remains crucial to assess and monitor cardiovascular risk of KD patients. Max-Z of CA correlates with PRPP modest inversely and might be used as a follow-up indicator of CA reserve during exercise after acute stage of KD.